Effect carbohydrates mouth rinse on repeated sprints time among UiTM Pahang footballers / Muhamad Zul Harith Mohd Zakaria Soh - Mohd Zakaria Soh, Muhamad Zul Harith (Faculty of Sport Science and Recreation, 2018)
The objective of this study is to evaluate the effect of carbohydrates mouth rinse on repeated sprint time among UiTM Pahang footballers. Fifteen footballer's players (age: 19.53 ± 1.50 years; weight: 61.33 ± 5.150 kg) were recruited in this' study. Subjects undergo three experimental trial conditions which are carbohydrate mouth rinse using 6.4 % dextrose (CHO), placebo using stevia (PLA) and control using plain water (CON). All subject need to rinse before repeated sprints start. Quantity for each solution is 25ml for every rinse. Subjects finish repeated sprints ability test consists of six sprints of 40 m (going! return = 20 m + 20 m), the 20s of passive recovery between every sprint. Repeated sprint time (RSA mean) was recorded. Oneway ANOVA was used to analyse this data and for repeated measures showed significant difference p;' 0.00 (p<O.05) in RSA mean (CHO =7.26s ± 0.96s; PLA = 7.34s ± 0.62s; CON = 7.41s ± 0.87s). The finding of this study showed that carbohydrate mouth rinse gives positive effect to the repeated sprint time among UiTM Pahang footballers.